The Education of an Idealist, A Memoir, y Tough Love, My Story of the Things Worth Fighting For - Dewar Viscarra, Diego Alberto (Foro Internacional, 2021)
Reseña de Samantha Power, The Education of an Idealist, A Memoir, Nueva York, Harper Collins, 2019, 552 pp. Susan Rice, Tough Love, My Story of the Things Worth Fighting For, Nueva York, Simon & Schuster, 2019, 482 pp.